Analysis of Merariq Kodeq Tradition Practiced by Sasak Indigenous People in Lombok Based on Max Weber and Georg Simmel's Theory - Testia F. Fitriyanti (Green Publisher Indonesia, 2023)
Sasak ethnic group still maintains the ancient tradition of abducted marriage or called Merariq, in which women are hidden in the homes of male relatives with the approval of traditional institutions. The tradition called 'merariq' initially required the consent of both parties and was only conducted under the strict supervision of traditional elders. The study aims to analyze Merariq Kodeq tradition practiced by Sasak indigenous people in Lombok from the point of view of max weber and georg simmel's theory. The study used a qualitative method with a literature review approach. The concept of social action initiated by Weber represents traditional Merariq tradition of Sasak indigenous people in Lombok. Compared to other sociologists, Weber's ideas are comprehensive.